Evaluation of real‐world effectiveness of perampanel in Japanese adults and older adults with epilepsy. Issue 1 (15th February 2022) - Inoue, Yushi; Sumitomo, Kenta; Matsutani, Kazuhiro; Ishii, Mika
Abstract: Objective . While previous studies have demonstrated the safety and effectiveness of perampanel (PER) in combination with other anti‐seizure medications in adult patients, data for older patients are limited. This study aimed to confirm real‐world safety and effectiveness of combination treatment with PER in Japanese patients with focal seizures with or without focal to bilateral tonic‐clonic seizures (FBTCS) or generalised tonic‐clonic seizures (GTCS) according to age subgroups (<65 and ≥65 years of age). Methods . This large‐sample prospective post‐marketing observational study included a 24‐52‐week observation period after the first PER treatment. Safety was assessed according to adverse drug reactions (ADRs) and efficacy was evaluated based on the 50% responder rate and rates of overall symptom improvement. Results . Among the 3, 808 patients who were enrolled, 3, 716 (3, 026 patients aged <65 years and 690 patients aged ≥65 years) and 3, 272 were included in the safety and efficacy analysis datasets, respectively. ADRs were reported for 1, 247 patients (33.6%) in the safety analysis dataset. Of these, 36.2% and 22.2% were aged <65 years and ≥65 years, respectively, and the most common ADRs were somnolence (11.6%, 5.5%) and dizziness (9.7%, 5.4%). The 50% responder rates in patients aged <65 years and those ≥65 years were 60.1% and 89.0% for those with focal aware seizures (FAS) with motor signs; 48.0% and 60.0% for FAS without motor signs; 47.4% and 80.2% for focal impaired awareness seizures; 70.8% and 93.4% for FBTCS; and 63.6% and 88.9% for GTCS, respectively. The improvement rates of symptoms/conditions were also higher in patients aged ≥65 years than those <65 years. Significance . PER was effective in reducing seizure frequency and was safe, especially in older patients. PER may be a clinical treatment option for older patients with seizure disorders.